Does Proprioception Influence Human Spatial Cognition? A Study on Individuals With Massive Deafferentation - Renault, Alix G.; Auvray, Malika; Parseihian, Gaetan; Miall, R. Chris; Cole, Jonathan; Sarlegna, Fabrice R. (Frontiers in Psychology, 2018)
When navigating in a spatial environment or when hearing its description, we can develop a mental model which may be represented in the central nervous system in different coordinate systems such as an egocentric or allocentric reference frame. The way in which sensory experience influences the preferred reference frame has been studied with a particular interest for the role of vision. The present study investigated the influence of proprioception on human spatial cognition. To do so, the abilities to form spatial models of two rare participants chronically deprived of proprioception (GL and IW) and healthy control participants were compared. Participants listened to verbal descriptions of a spatial environment, and the accuracy of their mental model was assessed with a distance-comparison task and a free-recall task. Given that the loss of proprioception has been suggested to specifically impair the egocentric reference frame, the deafferented individuals were expected to perform worse than controls when the spatial environment was described in an egocentric reference frame. Results revealed that in both tasks, one deafferented individual (GL) made more errors than controls while the other (IW) made less errors. On average, both GL and IW were slower to respond than controls, and reaction time was more variable for IW. GL but not IW was impaired compared to controls in visuo-spatial imagery, which was assessed with the Minnesota Paper Form Board test. Overall, the main finding of this study is that proprioception can influence the time necessary to use spatial representations while other factors such as visuo-spatial abilities can influence the capacity to form accurate spatial representations.